2001
DOI: 10.1086/323445
|View full text |Cite
|
Sign up to set email alerts
|

High-Mass, OB Star Formation in M51: [ITAL]HUBBLE SPACE TELESCOPE[/ITAL][ITAL]Hubble Space Telescope[/ITAL] Hα and P[CLC]a[/CLC]α Imaging

Abstract: We have obtained Ha and Paa emission-line images covering the central 3@È4@ of M51 using the WFPC2 and NICMOS instruments on the Hubble Space T elescope to study the high-mass stellar population. The pixels provide 4.6È9 pc resolution in M51, and the Ha/Paa line ratios are used to 0A .1È0A .2 obtain extinction estimates. A sample of 1373 Ha emission regions is cataloged using an automated and uniform measurement algorithm. Their sizes are typically 10È100 pc. The luminosity function for the Ha emission regions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
234
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(257 citation statements)
references
References 45 publications
22
234
1
Order By: Relevance
“…A scenario with a crowded population of PDRs overlapping along the line of sight is therefore more plausible. If a typical single OB stellar cluster emits up to 10 39 erg s À1 , the maximum value found by Scoville et al (2001) in M51 and also the luminosity of W49, then the number of single clusters to produce the Mrk 231 starburst luminosity of 10 12 L is k4 ; 10 6 . If these clusters are concentrated in a disk of radius 460 pc and thickness 25 pc (DS98), the mean distance between neighbor clusters is only P1.5 pc (see also Keto et al 1992).…”
Section: Discussionmentioning
confidence: 94%
“…A scenario with a crowded population of PDRs overlapping along the line of sight is therefore more plausible. If a typical single OB stellar cluster emits up to 10 39 erg s À1 , the maximum value found by Scoville et al (2001) in M51 and also the luminosity of W49, then the number of single clusters to produce the Mrk 231 starburst luminosity of 10 12 L is k4 ; 10 6 . If these clusters are concentrated in a disk of radius 460 pc and thickness 25 pc (DS98), the mean distance between neighbor clusters is only P1.5 pc (see also Keto et al 1992).…”
Section: Discussionmentioning
confidence: 94%
“…This is unlikely at such a low-frequency, because a similar thermal fraction has been found at 4.86 GHz (Fletcher et al 2011), while the thermal fraction must strongly decrease towards lower frequencies. Scoville et al (2001) found 1373 H ii emission regions exist within the central region with sizes up to 100 pc, and therefore thermal free-free absorption is expected. Recently, Adebahr et al (2013) observed a spectral flattening due to free-free absorption at 350 MHz in the core region of M82 where intense star formation is known to be occurring.…”
Section: Evidence Of Free-free Absorption In M 51mentioning
confidence: 97%
“…(See Scoville et al 2001 for more information about these observations.) The F187N and F190N filters, with effective wavelengths of 1.87 and 1.90 lm, contain Pa line and continuum images, respectively.…”
Section: Observationsmentioning
confidence: 99%
“…All positions were measured from the center of the galaxy, which was determined from the centroid of an H-band (F160W) image of M51 that was observed simultaneously with the Pa data (Scoville et al 2001). Since the nuclear region of M51 contains little molecular gas (see Fig.…”
Section: Logarithmic Spiralsmentioning
confidence: 99%